How Iranian Deaf Individuals Discuss Domestic Violence and Its Risk Factors - Golamrej Eliasi, Laleh; Tahzibi, Mahsa; Farahani, Hadi; Torkashvand Moradabadi, Mohammad (Scientific Research Publishing Inc., 2025)
This study aimed to explore the perceptions of Iranian deaf individuals regarding domestic violence against the deaf individuals and its associated risk factors in Iran. Data were gathered through interviews with 15 participants and analyzed using content analysis. Two main themes emerged regarding their perceptions of the types of domestic violence: 1) Emotional & Verbal, and 2) Physical & Economic. Additionally, two themes were identified concerning their perspectives on risk factors: 1) Deaf individuals & Deaf community, and 2) Family & Society. For future research, it is recommended to investigate the perspectives of Iranian deaf individuals’ families regarding domestic violence, its risk factors, and the necessary services for addressing this issue.